2015
DOI: 10.5206/cie-eci.v44i2.9273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concepts of Traditional Inuit Leadership and Effective School Leadership in Nunavut (Canada)

Abstract: The purpose of this paper is to document how educators living in Nunavut communities describe traditional Inuit leadership and effective school leadership. The data for this qualitative study were 24 semi-structured interviews, involving 14 teachers, vice-principals, and principals from Nunavut. Findings revealed that traditional Inuit leadership was about promoting the personal leadership skills, interests, and/or abilities of each community member, and it often involved Elders who fostered the linguistic, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As others have reported, Elders are consulted in community decisionmaking processes, and are often tasked with making important decisions given their wealth of vital traditional knowledge (Qitsualik, 1999;Barnaby et al, 2009). In the ways that they conduct themselves and through their expectations for the community, Elders demonstrate leadership, foster the social and spiritual wellness of youth, and disseminate culture, language, and knowledge (Preston et al, 2015). However,…”
Section: Lessons Learnedmentioning
confidence: 99%
“…As others have reported, Elders are consulted in community decisionmaking processes, and are often tasked with making important decisions given their wealth of vital traditional knowledge (Qitsualik, 1999;Barnaby et al, 2009). In the ways that they conduct themselves and through their expectations for the community, Elders demonstrate leadership, foster the social and spiritual wellness of youth, and disseminate culture, language, and knowledge (Preston et al, 2015). However,…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Building on traditional notions of leadership elders have explained that a person's leadership should be identified by others based on their skills as demonstrated over time. Each member of a community had the ability and responsibility to recognize the leadership potential and skills of fellow community members (Preston, Claypool, Rowluck, & Green, ).…”
Section: Discussionmentioning
confidence: 99%
“…Leadership is demonstrated in a variety of ways including trusting that one can fight for their own rights: pigunautinivit ; promoting and building trust in cultural ways of knowing and doing (Leon, ; Preston et al., ; Waddell et al., ), respecting and listening to others; and supporting others in developing their own leadership (Wesley‐Esquimaux & Calliou, ). Supporting this personal strength and confidence in oneself and in one's culture allows for people to come together and courageously share their thoughts and build a collective foundation to work as a team (Tagalik, ; Waddell et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Berger's (2007) research showed that Inuit parents and caregivers want the presence of Inuit culture, language, and Elders in schools. Research on the topic of educational leadership in Nunavut indicates that effective school leaders promote teamwork and are people-focused (Preston, Claypool, Rowluck, & Green, 2015). Adopting a generalized review of quality education, Preston (2016b) recognized that successful Indigenous education is a holistic concept that is reflected within four main areas: (a) strong early childhood programs, (b) the existence of Indigenous pedagogy, language, and culture throughout Kindergarten to Grade 12, (c) the existence of postsecondary educational opportunities imbued with Indigenous perspectives, and (d) the existence of productive federal, provincial/territorial, and Indigenous community partnerships.…”
Section: Literature Review: Successes Within Inuit Educationmentioning
confidence: 99%